Abundant storage protein depletion from tuber proteins using ethanol precipitation method: Suitability to proteomics study. Issue 10 (13th April 2015) - Lee, Hye Min; Gupta, Ravi; Kim, Sun Hyung; Wang, Yiming; Rakwal, Randeep; Agrawal, Ganesh Kumar; Kim, Sun Tae; Lüthje, Sabine; Deswal, Renu; Agrawal, Ganesh Kumar
<x xml:space="preserve">Abstract</x> High‐abundance proteins (HAPs) hamper in‐depth proteome study necessitating development of a HAPs depletion method. Here, we report a novel ethanol precipitation method (EPM) for HAPs depletion from total tuber proteins. Ethanol showed a dose‐dependent effect on depletion of sporamin from sweet potato and patatin from potato tubers, respectively. The 50% ethanol was an optimal concentration. 2DE analysis of EPM‐prepared sweet potato proteins also revealed enrichment of storage proteins (SPs) in ethanol supernatant (ES) resulting in detection of new low‐abundance proteins in ethanol pellet (EP), compared to total fraction. The ES fraction showed even higher trypsin inhibitor activity than total proteins, further showing the efficacy of EPM in enrichment of sporamin in ES fraction. Application of this method was demonstrated for comparative proteomics of two sweet potato cultivars (Hwang‐geum and Ho‐bac) and purification of SP (sporamin) in its native form, as examples. Comparative proteomics identified many cultivar specific protein spots and selected spots were confidently assigned for their protein identity using MALDI‐TOF‐TOF analysis. Overall, the EPM is simple, reproducible, and economical for depletion of SPs and is suitable for downstream proteomics study. This study opens a door for its potential application to other tuber crops or fruits rich in carbohydrates.